Variable speed drive control system as a controller for a 3-phase motor using function block diagram on zelio PLC - Triyono, Budi; Winarno, Basuki; Prakoso, Dimas Nur; Utama, Ferdiansyah Prasetya (Journal Geuthee of Engineering and Energy, 2025)
A 3-phase electric motor is one of the key components in industrial production processes. In industrial activities, electric motors play a significant role in the production process, as almost all machines in the industry use electric motors as their driving force. This type of motor is susceptible to overcurrent, caused either by an overload or excessive current. Common disturbances that may occur in a 3-phase electric motor include: high starting current, overcurrent, overvoltage, undervoltage, underfrequency, and short circuit undervoltage. A protection system is needed to minimize the losses caused by these disturbances, making it essential to conduct a protection system analysis to be installed on the motor. Using the Multi-Function Meter SMART 7KT as a device capable of detecting these disturbances and taking the necessary protective actions, the protection system employs a PLC (Programmable Logic Controller) and HMI (Human Machine Interface) as the interface for controlling and monitoring the protection system on the electric motor, communicated via Modbus RTU. Therefore, this protection system can safeguard the 3-phase electric motor from disturbances such as large starting current, overcurrent, undervoltage (-10% from normal voltage), overvoltage (+5% from normal voltage), and underfrequency. With this developed protection system, the risk of damage to critical or vital 3-phase electric motors can be minimized